4 - 6n = 60 - 2n <em>subtract 4 from both sides</em>
-6n = 56 - 2n <em>add 2n to both sides</em>
-4n = 56 <em>divide both sides by (-4)</em>
n = - 14
-7 + 11p = 3p - 47 <em>add 7 to both sides</em>
11p = 3p - 40 <em>subtract 3p from both sides</em>
8p = -40 <em>divide both sides by 8</em>
p = - 5
3a - 28 - 7a = 10a <em>combine like terms</em>
(3a - 7a) - 28 = 10a
-4a - 28 = 10a <em>add 28 to both sides</em>
-4a = 10a + 28 <em>subtract 10 from both sides</em>
-14a = 28 <em>divide both sides by (-14)</em>
a = - 2
17 - 5r + 9r = 12 + 6r - 1 <em>combine like terms</em>
17 + (-5r + 9r) = (12 - 1) + 6r
17 + 4r = 11 + 6r <em>subtract 17 from both sides</em>
4r = -6 + 6r <em>subtract 6r from both sides</em>
-2r = -6 <em>divide both sides by (-2)</em>
r = 3
8(y - 7) = -2(y + 3) <em>use distributive property: a(b + c) = ab + ac</em>
(8)(y) + (8)(-7) = (-2)(y) + (-2)(3)
8y - 56 = -2y - 6 <em>add 56 to both sides</em>
8y = -2y + 50 <em>add 2y to both sides</em>
10y = 50 <em>divide both sides by 10</em>
y = 5
-3(8k + 5) = 3(9 - k) <em>use distributive property: a(b + c) = ab + ac</em>
(-3)(8k) + (-3)(5) = (3)(9) + (3)(-k)
-24k - 15 = 27 - 3k <em>add 15 to both sides</em>
-24k = 42 - 3k <em>add 3k to both sides</em>
-21k = 42 <em>divide both sides by (-21)</em>
k = -2
2(3v - 5) = 2(v - 11) - 4 <em>use distributive property: a(b + c) = ab + ac</em>
(2)(3v) + (2)(-5) = (2)(v) + (2)(-11) - 4
6v - 10 = 2v - 22 - 4
6v - 10 = 2v - 26 <em>add 10 to both sides</em>
6v = 2v - 16 <em>subtract 2v from both sides</em>
4v = -16 <em>divide both sides by 4</em>
v = -4
-2/3 (15x + 3) -3x - 9 <em>use distributive property: a(b + c) = ab + ac</em>
= (-2/3)(15x) + (-2/3)(3) - 3x - 9
= (-2)(5x) - 2 - 3x - 9
= -10x - 2 - 3x - 9 <em>combine like terms</em>
= (-10x - 3x) + (-2 - 9)
= -13x - 11
3(1 - 9a) + 22a = 2(2a - 9) - 15
<em>use distributive property: a(b + c) = ab + ac</em>
(3)(1) + (3)(-9a) + 22a = (2)(2a) + (2)(-9) - 15
3 - 27a + 22a = 4a - 18 - 15 <em>combine like terms</em>
3 + (-27a + 22a) = 4a + (-18 - 15)
3 - 5a = 4a - 33 <em>subtract 3 from both sides</em>
-5a = 4a - 36 <em>subtract 4a from both sides</em>
-9a = -36 <em>divide both sides by (-9)</em>
a = 4
-3(3m - 10) - 7 = -5(m + 1) + 3m
<em>use distributive property: a(b + c) = ab + ac</em>
(-3)(3m) + (-3)(-10) - 7 = (-5)(m) + (-5)(1) + 3m
-9m + 30 - 7 = -5m - 5 + 3m <em>combine like terms</em>
-9m + (30 - 7) = (-5m + 3m) - 5
-9m + 23 = -2m - 5 <em>subtract 23 from both sides</em>
-9m = -2m - 28 <em>add 2m to both sides</em>
-7m = -28 <em>divide both sides by (-7)</em>
m = 4